MANAJEMEN BLACK TRIANGLE DALAM KEDOKTERAN GIGI ESTETIK: LITERATUR REVIEW - Afdalia Annisa; Arni Irawaty Djais (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2021)
Introduction: The black triangle is a condition where the interdental papila does not cover the space between teeth which can interfere with aesthetics, pronunciation and cause food impaction, so preservation of papila in the aesthetic area is something that must be considered in periodontal treatment. This article aims to review the literature on definitions, etiology, classification, and various considerations in handling black triangle cases in aesthetic dentistry. Review: Interdental papilae not only function as biological barriers for the periodontal structure beneath but also have an important role in aesthetics. Handlers in black triangle cases include non-surgical involves crossdepartment (Periodontia, Orthodontia, Conservation) and surgical. The etiology of interdental papila loss is multifactorial, so it is important to establish an adequate diagnosis to obtain an appropriate treatment plan. Non-surgical techniques can be performed by making prosthesis, restoration, and orthodontic treatment. While surgical techniques include reconstructive, preservation, and recontouring of interdental papilae. Conclusion: Black triangle treatment can provide maximum results by considering various factors, both etiology, appropriate treatment plan, and alternative treatments so that it can provide satisfaction for patients.